Factors affecting the sleep of one-year-olds : a pilot study using objective monitoring of New Zealand infants : a thesis presented in partial fulfilment of the requirements of the degree of Master of Science in Psychology at Massey University, Wellington, New Zealand - Gibson, Rosemary H (Massey University, 2009)
Sleep takes time to mature and in infancy the structure and cycle of sleep differs greatly to that of adults. Data concerning normative sleep of infants is lacking due to few studies using objective measures. Factors affecting infants' sleep are both intrinsic and extrinsic in nature. The causes of problematic sleep are not well understood. This study aimed to pilot a methodology involving 1 week of actigraphy monitoring of 1-year-olds, as well as collecting normative data concerning sleep and sleep ecology through questionnaires and diaries. Potential factors contributing to sleep quantity, quality and maturation were investigated. Sleeping problems were reported in 35% of the sample of 52 Wellington infants. Current breastfeeding, time awake at night, and poor evening mood were all associated with problem sleep. Short sleep duration and more instances of being put to bed were also significant predictors of reporting problem sleep. Infants were typically rated in a poorer mood and exhibited more bedtime problems at the weekend. Longer sleep onset latencies and poorer sleep efficiency were identified by actigraphy on weekend evenings. The timing of sleep did not differ between genders or between week days and weekends, or childcare and non-childcare days. Mixed model analysis of variance indicated that the maturation and quality of sleep were significantly correlated with age and stages of cognitive and motor development. Sleep duration did not correlate with ponderal index, possibly due to the young age group as well as underrepresentation of short sleeping or overweight infants. Results support previous studies in western societies and autonomous sleeping is common. Potential mechanisms behind relationships between sleep and feeding, temperament and development are discussed. Strengths and limitations of methods and procedures are assessed. Actigraphic recording of 1-year-olds is demonstrated to be a useful and reliable tool for studying sleep of infants and the results contribute to normative data. Future studies in NZ should consider recruiting a more representative sample and incorporate a longitudinal design to further assess the relationships highlighted here and in previous research.
Keywords: Infants; Sleep; Physiological aspects